Sumerian model contracts from the Old Babylonian period in the Hilprecht Collection Jena - Spada, Gabriella (Texte und Materialien der Frau Professor Hilprecht Collection of Babylonian Antiquities im Eigentum der Friedrich-Schiller-Universität Jena, 2018)
Cover -- Title Page -- Copyright -- Table of Contents -- Body -- Vorwort des Herausgebers -- Preface by the Author -- 1. Introduction -- 1. The texts -- 2. Organization of the volume -- 2. Catalogue and Concordance -- Catalogue -- Concordance of duplicates to the model contracts -- 3. The text edition -- 1. Prisms -- Text n° 1. -- Text n° 2. -- Text n° 3. -- 2. Type I tablet -- Text n° 4. -- 3. Type II tablets -- Text n° 5. -- Text n° 6. -- Text n° 7. -- Text n° 8. -- Text n° 9. -- 4. Unidentified type of tablets -- Text n° 10. -- Text n° 11. -- 4. Indexes -- 1. Personal names -- 2. Deities -- 3. Toponyms -- 4. Glossary -- a. Sumerian words -- b. Akkadian word -- 5. Bibliography -- Bibliographical abbreviations -- Bibliography -- Plates -- 1. Handcopies -- 2. Photographs